"A Necessary Preparative to the Study of Philosophy": A Positive Appraisal of Descartes' Universal Doubt. Issue 3 (19th May 2022) - Badía Cabrera, Miguel A.
ABSTRACT: My main concern in this article is to arrive at a clear view of the nature, extent, and value of Descartes' universal doubt, not to determine whether Hume's critique of Cartesian doubt is compelling. It is rather to reflect on Descartes' own assessment of the matter in order to explain why Hume was right in recommending Descartes' doubt in the Meditations, when reasonably understood, as "a necessary preparative to the study of philosophy." This task will be discharged, first, through an analysis of the Meditations and other works of Descartes connected with this topic; and second, by an exploration of the effect that the radical and extensive doubt undertaken by Descartes in the Meditations has elicited from generations of students, particularly from those inclined to philosophize, namely the sudden intellectual upheaval and awakening of their critical faculties. I argue that the universal, "hyperbolic" doubt is not artificial or rhetorical, or a mere heuristic construct to secure Descartes' metaphysical principles. Instead, it is but a development and methodic refinement of a natural predisposition of the human mind that manifests itself early in the serious, encompassing doubts children entertain on certain occasions.